The Impact of Calcium on Chronic Total Occlusion Management - Claudia Cosgrove; Kalaivani Mahadevan; James C Spratt; Margaret McEntegart (Interventional Cardiology: Reviews, Research, Resources)
Coronary artery calcification is prevalent in chronic total occlusions (CTO), particularly in those of longer duration and post-coronary artery bypass. The presence of calcium predicts lower procedural success rates and a higher risk of complications of CTO percutaneous coronary intervention. Adjunctive imaging, including pre-procedural computed tomography and intracoronary imaging, are useful to understand the distribution and morphology of the calcium. Specialised guidewires and microcatheters, as well as penetration, subintimal entry and luminal re-entry techniques, are required to cross calcific CTOs. The use of both atherectomy devices and balloon-based calcium modification tools has been reported during CTO percutaneous coronary intervention, although they are limited by concerns regarding safety and efficacy in the subintimal space.